Human Monkeypox: An Emerging and Neglected Viral Zoonosis of Public Health Concern - Kasarla, Rajeshwar Reddy (Journal of Universal College of Medical Sciences, 2022)
The world has witnessed several emerging and re-emerging infectious diseases. The recent COVID-19 pandemic is one of the biggest incidents that happened in human history. The war against COVID-19 is not over yet, and the sudden and unexpected outbreak of monkey pox has begun to invoke panic worldwide. Monkeypox is a rare viral zoonotic disease that occurs primarily in tropical rainforest areas of central and West Africa.